2017
DOI: 10.1002/mp.12248
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Monte Carlo study of106Ru/106Rh ophthalmic plaques including the106Rh gamma spectrum

Abstract: The influence of the Rh gamma spectrum is not relevant for clinical purposes, thus validating the common assumption from the literature. However, for simulations at large distances from the plaques, such as for radiation shielding assessment and estimation of dose to personnel, the gamma spectrum from Rh must be taken into account to obtain accurate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In order to find the cause of the isodose disagreement between film measurements and MC calculations in the low-dose region, some simulations were carried out, including the Ru/Rh-106 gamma spectrum, obtaining results similar to those of Hermida-López et al [ 34 ], who reported an insignificant contribution of the gamma spectrum for clinical depths (below 10 cm). Besides gamma contribution, there are at least two other factors that may have a significant impact on the isodose distributions: (a) The measurement depth as to film measurements and (b) the inactive rim size parameter as to MC simulations.…”
Section: Discussionmentioning
confidence: 75%
“…In order to find the cause of the isodose disagreement between film measurements and MC calculations in the low-dose region, some simulations were carried out, including the Ru/Rh-106 gamma spectrum, obtaining results similar to those of Hermida-López et al [ 34 ], who reported an insignificant contribution of the gamma spectrum for clinical depths (below 10 cm). Besides gamma contribution, there are at least two other factors that may have a significant impact on the isodose distributions: (a) The measurement depth as to film measurements and (b) the inactive rim size parameter as to MC simulations.…”
Section: Discussionmentioning
confidence: 75%
“…Such conditions would certainly aid in the volatilization and dispersion of otherwise nonvolatile ruthenium species. For a facility undertaking the purification of fission products from spent nuclear fuel for commercial gain, it is hard to ignore the potential profit afforded by obtaining 106 Ru in high-specific activity, considering its long-standing medical use in the development of brachytherapy plaques for the treatment of eye cancer (53,54). For this application, it is commonly electrodeposited from solution onto silver, along with the addition of carrier RuCl 3 (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…For a facility undertaking the purification of fission products from spent nuclear fuel for commercial gain, it is hard to ignore the potential profit afforded by obtaining 106 Ru in high-specific activity, considering its long-standing medical use in the development of brachytherapy plaques for the treatment of eye cancer (53,54). For this application, it is commonly electrodeposited from solution onto silver, along with the addition of carrier RuCl 3 (54,55). Since this requires a highly soluble form of 106 Ru, it makes sense to invoke a reductive technique that generates polychlorinated Ru(III/IV) species with a high degree of radiopurity and aqueous solubility, rather than the vast majority of passivation techniques that ultimately produce the highly insoluble RuO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The considered emitting energy spectrum was the one corresponding to the beta transitions from 106 Rh to 106 Pd, which is provided in ICRU Report 72 14 . The photon component produced by transitions to the ground state of 106 Pd was ignored as it is not relevant for clinical purposes 15 …”
Section: Methodsmentioning
confidence: 99%